1982
DOI: 10.1111/j.1464-410x.1982.tb13528.x
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Management of Bilharzial Strictures of the Ureter

Abstract: Twenty-one ureteric strictures due to bilharzia have been treated surgically in 13 patients. Two required nephrectomy; 19 had direct ureteric reimplantation into the dome of the bladder after excision of the strictured segment of ureter. A simple technique of reimplantation into the dome of the bladder is described and early results have justified its further use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Vesico-ureteric reflux is unusual in bilharziasis, and simple domal vesico-ureteric implantation has been reported to be safe and non-reflux-inducing (Mee and Youssef, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vesico-ureteric reflux is unusual in bilharziasis, and simple domal vesico-ureteric implantation has been reported to be safe and non-reflux-inducing (Mee and Youssef, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In vesico-ureteric implantation, since only the most involved distal ureteric segment is excised and the remaining diseased ureter is used for the anastomosis, there is a risk of re-stenosis (Mee and Youssef, 1982). Ileal loop replacement has a limited place in the management of ureteric strictures and is associated with significant morbidity and mortality (Weinberg, 1970;Ghoneim and Shoukry, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate of Boari flap surgery for extensive bilharzial ureteric strictures was highly satisfactory when compared with the success rates of other surgical approaches (Maged, 1971 ;Smith et al, 1977;Elbaz and Badr, 1982;Mee and Youssef, 1982;Bazeed et al, 1983;A1 Shukri and Alwan, 1983;Jacobson et al, 1987;Rady and Rady, 1987;Wishahi, 1987;Awad et al, 1989).…”
mentioning
confidence: 88%
“…In the absence of severe structural damage to the affected ureters, such patients are usually managed by vesicoureteric reimplantation, but the gross dilatation of the ureters and the intense periureteritis make it difficult and dangerous to use an anti-refluxing type of reimplantation by submucosal tunnelling. Fam (1964) Table Salient Features of the 10 Patients to-side ureterovesical anastomosis which has been widely employed in bilharzial surgery (Ghoneim et ai., 1971;Mee and Youssef, 1982). Urquhart-Hay et al (1977) have recently reported the anti-reflux potential of vesicoureteric reimplantation by constructing a nipple from a dilated ureter without submucosal tunnelling.…”
mentioning
confidence: 99%